Find it quick - handbook on cults & new religions - Rhodes, Ron (Harvest House Publishers, 2005)
"Were most cults and new religions simply passing fads of the late-twentieth century, or are some of them still growing today? What new sects have emerged, and what dangers do they present? How should Christians respond? Bible teacher and apologetics expert Ron Rhodes has cataloged 40 groups in this concise and easy-to-use handbook. Readers will appreciate Ron's thorough research and his reader-friendly style. His brief examination of each group includes: a short history of the sect or new religion; an explanation of the group's major doctrines; the Christian apologetic response. This informative guide includes a list of 'Apologetic Power Points, ' which provides readers with a fast-paced summary of the foundational truths of biblical Christianity"--Amazon.com